Amberlite XAD-4 based electrochemical sensor for diclofenac detection in urine and commercial tablets - Shanbhag M.M.; Ilager D.; Mahapatra S.; Shetti N.P.; Chandra P. (My University, 2025)
Amberlite XAD-4 (XAD-4) is a polymeric adsorbent that is a crosslinked polystyrene copolymer resin known for its durability, chemical stability, and large surface area. Diclofenac sodium (DIC) is a non-steroidal anti-inflammatory drug (NSAID) that has antipyretic and analgesic properties, commonly used in pain-associated treatments. Although DIC is a very important and clinically proven drug, it causes serious health issues when administered in overdose and may also be found in body fluids. Thus, it is essential to develop a method to detect the trace levels of DIC in various pharmaceutical and clinical samples to regulate the optimum dosage. In this study, we have developed a new electrochemical sensor for the investigation and recognition of DIC by modifying the carbon paste with XAD-4 (XAD-4/CPE). The DIC showed only an anodic peak and no cathodic peak in the reverse scan indicating an irreversible reaction mechanism. The peak in the forward scan confirms the electrooxidation of DIC which was utilized for its testing in diverse matrices in this study. The developed sensor shows a high surface area and enhanced electrochemical signals compare to the bare carbon paste electrode (CPE). The developed electrode showed good selectivity, reproducibility, repeatability, and sensitivity with a detection limit value of 2.71 × 10−8M. The fabricated electrode was applied for direct detection of DIC in commercial tablets and urine samples, suggesting its wide applicability in clinics and pharmaceutical formulations. Interferences due to coexisting chemicals were investigated and stability of the designed sensor was also studied confirming its tremendous real-world applications. © 2021